2019
DOI: 10.3389/feart.2019.00281
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Heterogeneity of Mg, Mn, Na, S, and Sr in Benthic Foraminiferal Calcite

Abstract: The chemical composition of fossil foraminiferal shells (tests) is widely used as tracers for past ocean chemistry. It is, therefore, important to understand how different (trace) elements are transported and incorporated into these tests from adjacent seawater. The elemental distribution within the walls of foraminiferal tests might be used to differentiate between proposed transport mechanisms. Here, the microdistribution of Mg, Mn, Na, S, and Sr in tests of three species of foraminifera, known to have contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 95 publications
(168 reference statements)
0
23
0
Order By: Relevance
“…The overall trend is about three times more sensitive as observed for porcelaneous Amphisorus kudakajimensis (slope −0.01‰/°C; Maeda et al, 2019). Such a difference most likely reflects a difference in the biomineralization between these species, which is also evident in the contrasting Mg/Ca of these species: A. kudakajimensis typically has Mg/Ca ratios of ∼150 mmol/mol, whereas A. lessonii has an order of magnitude lower Mg/Ca ratio, typically of 20-30 mmol/mol (e.g., van Dijk et al, 2019a;Geerken et al, 2019). The sensitivity of the isotopic composition of incorporated Mg to temperature also varies between these species: A. lessonii being less sensitive (slopes of the calibration regression being 1.69 mmol/mol/°C in A. lessonii (van Dijk et al, 2019b) compared to 2.74 mmol/mol/°C in A. kudakajimensis (Maeda et al, 2017).…”
Section: Discussion δ 26 Mg In Marine Calcifiersmentioning
confidence: 99%
“…The overall trend is about three times more sensitive as observed for porcelaneous Amphisorus kudakajimensis (slope −0.01‰/°C; Maeda et al, 2019). Such a difference most likely reflects a difference in the biomineralization between these species, which is also evident in the contrasting Mg/Ca of these species: A. kudakajimensis typically has Mg/Ca ratios of ∼150 mmol/mol, whereas A. lessonii has an order of magnitude lower Mg/Ca ratio, typically of 20-30 mmol/mol (e.g., van Dijk et al, 2019a;Geerken et al, 2019). The sensitivity of the isotopic composition of incorporated Mg to temperature also varies between these species: A. lessonii being less sensitive (slopes of the calibration regression being 1.69 mmol/mol/°C in A. lessonii (van Dijk et al, 2019b) compared to 2.74 mmol/mol/°C in A. kudakajimensis (Maeda et al, 2017).…”
Section: Discussion δ 26 Mg In Marine Calcifiersmentioning
confidence: 99%
“…2B and S6). In the case of inter-CL Mg banding, the high and thin Mg bands are observed within or close to the "outer organic linings", intercalated with the outer calcitic layers (OCLs) 6,12,13,37 . Previously, the "intra-CL" Mg banding was considered as an exception for the spherically-shaped planktic foraminifer O. universa, whose last chamber was known to continue thickening after its formation 5,7 .…”
Section: Comparing Mn (Zn) and Mg Patterns The Parallel Mn-zn Bands mentioning
confidence: 99%
“…To unravel the Mn and Zn trace patterns, a nanometric spatial resolution and high elemental sensitivity by nano-imaging is required, and is achieved here by synchrotron X-ray Fluorescence analyses (XRF) 29 . In previous works, foraminifer intra-test elemental distribution mapping reached spatial resolutions of 85-500 nm for elemental concentrations at the 100 ppm level (nanoscale Secondary Ion Mass Spectrometry-NanoSIMS), or of 1 µm with minor element sensitivities (Synchrotron micro-XRF and Electron Probe Micro Analysis-EPMA) for concentrations relative to the average Ca signal 12,13 . We have focused our nano-XRF measurements on two sampling choices of the last chamber walls: full wall bulk (10 to 11 µm thick) and patterns in transverse sections across the wall (~ 1 µm thick).…”
mentioning
confidence: 99%
“…and Bulimina marginata, thin bands with high Mn/Ca are observed at the start of calcite lamellae (Van Dijk et al, 2019b), which could be due to absorption layers that are exposed to the surrounding seawater between chamber formation events, as hypothesized in Barras et al (2018). These high Mn/Ca layers are co-located with high Mg/Ca banding and are associated with a carbonateassociated species of Mn (Van Dijk et al, 2019b). Other processes related to seawater carbonate chemistry could also impact element incorporation (Ries et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…Barras et al (2018) found that the two benthic species Ammonia tepida and Bulimina marginata, cultured under the same conditions, have a Mn partitioning of 0.08 and 0.6, respectively, an offset of one order of magnitude. Incorporation of Mn appears to be coupled to that of Mg (Van Dijk et al, 2019b), similar to what is observed for other elements (Van Dijk et al, 2017b), possibly due to crystal lattice strain (Mucci and Morse, 1983;Evans et al, 2015) or simultaneous uptake (Van Dijk et al, 2019a). Even if the relative sensitivity of Mn/Ca to oxygenation is the same for different species, as suggested for certain proxies (e.g., S/Ca; Van Dijk et al, 2017a), the absolute Mn/Ca value is still needed for reconstruction of oxygenation.…”
Section: Introductionmentioning
confidence: 99%